Analysis of Inclusive Education Policy in Surabaya - Yuli Eka Purwanti; Budi Purwoko; Mufarrihul Hazin; Nabila Dwi Wahyu Santoso (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study analyzes the inclusive education policy in Surabaya and its impact on the performance of elementary school educators. Using a descriptive qualitative approach, data were collected through observation, interviews, and questionnaires, then analyzed using source triangulation. The findings reveal that educators show strong commitment and apply various learning strategies to accommodate students with special needs. However, significant challenges persist, including limited facilities, a shortage of qualified personnel, and insufficient specialized training. In addition, factors such as high workload and social stigma hinder the effective implementation of inclusive education. Despite these obstacles, the policy demonstrates promising potential through systemic support, collaboration with parents, and the contribution of special assistant teachers. To achieve greater effectiveness, improvements in school infrastructure, continuous professional development, and more inclusive educational environments are essential. Strengthening stakeholder cooperation between schools, local governments, and communities will further enhance the sustainability and success of inclusive education in Surabaya.